BIOCHEMICAL AND MICROBIOLOGICAL IDENTIFICATION OF COW'S MILK FOR THE MANUFACTURE OF SOFT CHEESE - F., Mesli*1; A., . Lazouni Hamadi2 (university of eloued جامعة الوادي, 2019)
Our work focuses on the study of the technological process of making a soft cheese; five samples were the subject of our investigations. These were analyzed during the period of high lactation (January to March 2017). Microbiological and biochemical tests were carried out on five microbial groups and pathogenic organisms. Biochemical identifications are performed to target the most likely bacteria. All the results have been compared is validated by contribution to experimental results as well as theoretical work show a compatibilities and validation by contribution to the norm. The microbiological analyzes of the five samples studied show the total absence of the seeds sought with the exception of FTAM, with a low presence not exceeding the threshold of acceptability. These results indicate that the samples of the milk used in the manufacture of soft cheese are very good from a microbiological point of view.
artical
Keywords: Milk, Microbiology, Identification